Panoptic Life in Orwell’s Nineteen Eighty Four - Sharma, Pradeep (Humanities and Social Sciences Journal, 2023)
This article discusses panopticon as a controlling mechanism that moulds the conduct of Winston Smith and Julia in George Orwell’s political novel 1984. It aims at examining the government tactics; panopticon, that exerts power for controlling and constructing the subjectivity. Taking the reclose to Jeremy Bentham’s penal theory of panopticon, Michel Foucault appropriates his notion of biopolitics to remap how power constitutes the subjectivity of the population. This article probes into the state paradigms that indoctrinates and makes people docile via panopticon in 1984 to subject Julia and Smith to power and their rendering of self-subjection as the political outcasts. Finally, the surveillance telescreen of the Big Brother instantiates to fortify absolute regime leading it to institutionalized punishment and outlawry of Smith and other in Orwellian novel.